Process improvement in manufacturing company in Malaysia - Tan, Peggi Sook Tin; Sabar, Rohafiz (2012)
Nowadays, every company will conduct their improvement activity in order to compete with other companies especially in the same industry.The studies identify the implementation of process improvement that improves the operations of manufacturing company in Malaysia.There had some techniques and tools that can used to improve the quality and productivity, reduce the operation cost, cycle time, and also reduce waste.This research used the quantitative methods for the data collection and used likert scaled questions and ended questions.The result shows that most of the peoples are agree the company should implement their process improvements.